Identification of novel DNA-damage tolerance genes reveals regulation of translesion DNA synthesis by nucleophosmin - Ziv, Omer; Zeisel, Amit; Mirlas-Neisberg, Nataly; Swain, Umakanta; Nevo, Reinat; Ben-Chetrit, Nir; Martelli, Maria Paola; Rossi, Roberta; Schiesser, Stefan; Canman, Christine E.; Carell, Thomas; Geacintov, Nicholas E.; et al. (Nature communications, 2014)
Cells cope with replication-blocking lesions via translesion DNA synthesis (TLS). TLS is carried out by low-fidelity DNA polymerases that replicate across lesions, thereby preventing genome instability at the cost of increased point mutations. Here we perform a two-stage siRNA-based functional screen for mammalian TLS genes and identify 17 validated TLS genes. One of the genes, NPM1 , is frequently mutated in acute myeloid leukaemia (AML). We show that NPM1 (nucleophosmin) regulates TLS via interaction with the catalytic core of DNA polymerase-η (polη), and that NPM1 deficiency causes a TLS defect due to proteasomal degradation of polη. Moreover, the prevalent NPM1c+ mutation that causes NPM1 mislocalization in ~30% of AML patients results in excessive degradation of polη. These results establish the role of NPM1 as a key TLS regulator, and suggest a mechanism for the better prognosis of AML patients carrying mutations in NPM1. Cells cope with replication-blocking DNA lesions by translesion DNA synthesis (TLS) polymerases, including polη. Here, the authors show that NPM1 , a gene frequently mutated in acute myeloid leukaemia, protects polη from proteasomal degradation, and that NPM1 deficiency causes a TLS defect.